Blood flow responses to mild-intensity exercise in ectopic versus orthotopic prostate tumors: dependence upon host-tissue hemodynamics and vascular reactivity - Garcia, Emmanuel (Kansas State University, 2016)
Given the critical role of tumor O₂ delivery on patient prognosis and the rise in preclinical exercise-oncology studies, we investigated tumor and host-tissue blood flow at rest and during exercise as well as vascular reactivity using a rat prostate cancer model grown in two transplantation sites. Methods. In male COP/CrCrl rats, blood flow (via radiolabeled microspheres) to prostate tumors (R3327-MatLyLu cells injected in the left flank (ectopic) or ventral prostate (orthotopic)) and host-tissue was measured at rest and during a bout of mild-intensity exercise. Alpha-adrenergic vasoconstriction to norepinephrine (NE: 10⁻⁹ to 10⁻⁴ M) was determined in arterioles perforating the tumors and host-tissue. To determine host-tissue exercise hyperemia in healthy tissue, a sham-operated group was included. Results. Blood flow was lower at rest and during exercise in ectopic tumors and host-tissue (subcutaneous adipose) versus the orthotopic tumor and host-tissue (prostate). During exercise, blood flow to the ectopic tumor significantly decreased by 25 ± 5%, whereas flow to the orthotopic tumor increased by 181 ± 30%. Maximal vasoconstriction to NE was not different between arterioles from either tumor location. However, there was a significantly higher peak vasoconstriction to NE in subcutaneous adipose arterioles (92 ± 7%) versus prostate arterioles (55 ± 7%). Establishment of the tumor did not alter host-tissue blood flow from either location at rest or during exercise. Conclusion. These data demonstrate blood flow in tumors is dependent on host-tissue hemodynamics and that the location of the tumor may critically affect how exercise impacts the tumor microenvironment and treatment outcomes.
Keywords: Kinesiology; Oncology; Tumor; Hemodynamics